Determinan Akuntabilitas Pengelolaan Keuangan Daerah dengan Sistem Pengendalian Intern sebagai Variabel Moderasi - Anggraini, Sinta; Hermanto, Hermanto; Hidayati, Siti Aisyah (E-Jurnal Akuntansi; Vol 31 No 8 (2021), 2021)
This study aims to analyze the effect of financial statement presentation, financial statement accessibility, and commitment to financial management accountability moderated by internal control system. The population of this research is 32 OPD, 40 DPRD members, and 20 Mataram City government NGOs. The results show that the internal control system strengthens the presentation of financial statements and commitments, but weakens the accessibility to financial accountability. The implication of this research can provide input for local government to make further policies related to regional financial management . Keywords: Presentation of Financial Statements; Accessibility of Financial Statements; Organizational Commitment; Accountability of Regional Financial Management; Internal Control System.